Theoretical study on the correlation of swelling peaks between neutron and heavy ion irradiated 15-15Ti stainless steel - Wen, A.-Li; Zhang, Qiao-Li; Fan, Ping; Ma, Hai-Liang; Li, Ke; Ren, Cui-Lan; Huang, He-Fei; Zhu, Sheng-yun; Yuan, Da-Qing (Journal of applied physics, 2022)
Titanium-modified austenitic stainless steels (15-15TiSS) are currently used as the fuel cladding material of fast reactors, which are subject to higher radiation damage during their application. In this work, the radiation-induced swelling of 15-15TiSS under a fast reactor neutron and heavy ion irradiation conditions was studied by the rate theory (RT). The simulated swelling properties of 15-15TiSS under fast neutron conditions were calculated initially. The swelling peak, swelling rates, and swelling-related microstructural properties are consistent with the neutron irradiation results, indicating that the selected RT model and material parameters are reasonable. Then, the swelling properties of 15-15TiSS under various damage rates were predicted by changing the radiation damage rates from 1 × 10−6 to 1 × 10−3 dpa/s. It shows that swelling peaks are strongly dependent on temperature and the swelling peaks shift ∼50 °C toward the higher temperature with each order of magnitude increase of defects generation rate. The swelling rates and swelling-related defect evolution at 1 × 10−3 dpa/s (with a swelling peak temperature of 590 °C) are consistent with that under neutron irradiation with 1 × 10−6 dpa/s (with a swelling peak temperature of 460 °C). At length, the RT-predicted heavy ions irradiation results were verified by the previous positron annihilation lifetime spectroscopy results of ions irradiated 15-15TiSS. It indicates that heavy ion irradiation can be used to study the radiation effect of materials under neutron irradiation and should be a feasible technique used in the further screening of radiation-resistant materials.